Asignación de frecuencias en telefonía celular aplicando el problema de coloración robusta - Lara-Velázquez, Pedro (2009)
The Robust Coloring Problem (RCP) is a NP-Hard Problem for which fast and efficient heuristic algorithms has been developed. In this work we present as a PCR the problem of assignment of frequencies for a cellphone grid. Some instances for this model are proposed and solved using a GRASP algorithm. Evidence shows that the intermittent interruptions in service can be eliminated and the overall capacity can be increased in approximately 25%.